The Role of School Environment in Maintaining the Consistency of Hijab Wearing in Students: Social Challenges and Solutions for Religious Education in the Modern Era - Zubaidah; M. Aqil Fahmi Sanjani; Uswatun Hasanah; Moh Nur Fauzi; Muhammad Abrori (Journal of Social Studies and Education, 2024)
This research focuses on the understanding and challenges faced by students in maintaining the consistency of wearing hijab, as well as the role of schools in supporting the understanding and practice of hijab among students. This research uses a qualitative approach with a case study design, which combines data collection techniques of interview, observation, and documentation. Respondents involved in this study consisted of students, religious teachers, and school staff who play a role in religious activities. The data obtained were analyzed through the stages of reduction, display, and verification to draw valid conclusions. The results showed that the majority of students in both schools viewed hijab as an important expression of religious identity and as a form of modesty. However, they face challenges in maintaining consistency in wearing the hijab, mainly due to the influence of peer pressure, social media, and social norms outside the school environment. In addition, this study also found that religious education programs implemented in schools have a significant role in shaping the understanding and practice of hijab among students. Support from peers, family, and school environment proved to be important in encouraging students to maintain wearing hijab. The implications of this study suggest that a supportive school environment, both structurally and socially, can strengthen students' consistency in wearing hijab, while enriching their understanding of religious values. This research provides important insights for the development of a more holistic religious education curriculum.